Alkyl-Glycerol Rescues Plasmalogen Levels and Pathology of Ether-Phospholipid Deficient Mice - Brites, Pedro; Ferreira, Ana Sofia; Ferreira da Silva, Tiago; Sousa, Vera F.; Malheiro, Ana R.; Duran, Marinus; Waterham, Hans R.; Baes, Myriam; Wanders, Ronald J. A. (PLOS ONE, 2011)
A deficiency of plasmalogens, caused by impaired peroxisomal metabolism affects normal development and multiple organs in adulthood. Treatment options aimed at restoring plasmalogen levels may be relevant for the therapy of peroxisomal and non-peroxisomal disorders. In this study we determined the in vivo efficacy of an alkyl glycerol (AG), namely, 1-O-octadecyl-rac-glycerol, as a therapeutic agent for defects in plasmalogen synthesis. To achieve this, Pex7 knockout mice, a mouse model for Rhizomelic Chondrodysplasia Punctata type 1 characterized by the absence of plasmalogens, and WT mice were fed a control diet or a diet containing 2% alkyl-glycerol. Plasmalogen levels were measured in target organs and the biochemical data were correlated with the histological analysis of affected organs. Plasmalogen levels in all peripheral tissues of Pex7 KO mice fed the AG diet for 2 months normalized to the levels of AG fed WT mice. In nervous tissues of Pex7 KO mice fed the AG-diet, plasmalogen levels were significantly increased compared to control fed KO mice. Histological analysis of target organs revealed that the AG-diet was able to stop the progression of the pathology in testis, adipose tissue and the Harderian gland. Interestingly, the latter tissues are characterized by the presence of lipid droplets which were absent or reduced in size and number when ether-phospholipids are lacking, but which can be restored with the AAG treatment. Furthermore, nerve conduction in peripheral nerves was improved. When given prior to the occurrence of major pathological changes, the AG-diet prevented or ameliorated the pathology observed in Pex7 KO mice depending on the degree of plasmalogen restoration. This study provides evidence of the beneficial effects of treating a plasmalogen deficiency with alkyl-glycerol.